Analysis behavior of soil resistivity profiling base on UniMAP condition - Arshad S.N.M.; Wahib A.H.; Halim N.H.; Yousof M.F.M.; Ariffen A.M.; Wooi C.L.; Abd Rahman M.S. (Institute of Physics Publishing, 2023)
Lightning; MATLAB; Soils; Electrical equipment; Grounding systems; High voltage; Lightning strikes; Matlab- software; Soil resistivity; Soil structure; Electric grounding